Contribution Of Parental And Teachers' Guidance Towards Independent Behavior Of Elementary School Children - Br Sembiring, Vidiani; Ndona, Yakobus; Gultom, Ibrahim (Mataram University, 2024)
The contribution of parental and teacher guidance to the independent behavior of elementary school children needs to be considered carefully. Although this guidance plays an important role in child development, overprotective attitudes, lack of consistency, and the influence of the social and technological environment can hinder children's independence. This study uses the library research method. The data collection technique in this study was carried out through documentation review or document review. To ensure the validity of the data in this study, the source triangulation technique was used. The results of the study showed that 1). The Role of Parents in Shaping the Independence of Elementary School Children is to play an important role in shaping children's independence, with democratic parenting patterns proven to be more effective in encouraging independence than authoritarian or permissive parenting patterns. 2). The Role of Teachers in Developing the Independence of Elementary School Children is to develop student independence through a teaching approach that encourages responsibility and active participation. By giving individual and group assignments, and involving students in projects and class discussions, teachers help students learn independently. 3). Collaboration of Parents and Teachers in Developing Independence of Elementary School Children is that parents and teachers play an important role in supporting the development of independence of elementary school children. Open communication and good cooperation between the two parties ensure that children receive consistent guidance, both at home and at school.